QUALITATIVE CHARACTERISTICS OF HAMBURGERS AND KAFTAS PRODUCED FROM MEAT OF LAMBS FED GLYCERINE - Borghi, T. H. [UNESP]; Silva Sobrinho, A. G. [UNESP]; Merlim, F. A. [UNESP]; Almeida, F. A. [UNESP]; Zeola, N. M. B. L. [UNESP]; Cirne, L. G. A.; Lima, A. R. C. [UNESP] (Inst Zootecnia, 2016)
The objective of this study was to evaluate the qualitative (pH, color, water activity, water retention capacity, cooking loss, and shear force) and sensory characteristics of processed meat produced from less noble cuts of the carcasses of lambs fed diets containing sugarcane as roughage and concentrates with and without 10 and 20% glycerine. Neck and rib meat of 30 lambs slaughtered at a body weight of 32.0 +/- 0.2 kg was used for the elaboration of hamburgers and koftas. Except for color, the inclusion of glycerine in the lamb diet did not influence (P> 0.05) the qualitative traits evaluated. The inclusion of glycerine reduced the redness (from 10.07 to 8.89, P= 0.044) and yellowness (from 5.97 to 5.07, P= 0.039) of hamburgers. The same effect was observed for the redness (from 10.83 to 9.61, P= 0.031) and yellowness (from 5.86 to 5.12, P= 0.047) of koftas. The sensory characteristics evaluated were not influenced (P> 0.05) and the grades of overall acceptance ranged from 7.4 to 7.9. The inclusion of glycerine in the diet of lambs altered the color of processed meat products, but provided satisfactory sensory characteristics.
Keywords: alternative food; sensory analysis; hamburger; kafta